Early aseptic loosening in one design (3M-Capital) of cemented total hip replacement - Pandit, H; Hand, C; Ramos, J; Pradhan, N; Hobbs, N (2000)
This is a retrospective study of one particular design of cemented hip (the 3M - Capital) used in Great Britain in the early 90's. The study included 224 primary THRs performed over a period of 5 years (average follow-up: 38.4 months) using either monobloc (31) or modular (193) stems the former made of stainless steel and the latter of titanium alloy. A high incidence of early loosening of the femoral component was noticed with both types of stem (12.5% definite loosening, 11.16% possible loosening). Possible aetiologies are discussed. Thirty-five patients (15.6%) were listed for revision. Early failure with the use of the stainless steel implants version of this prosthesis is so far unreported. Patients with early loosening were heavier than those without loosening over the same period of follow up, which was statistically significant. Histological findings at the time of revision are also discussed. In early 1998 a national audit was initiated to locate all the patients with Capital hip implant and these are the results of the study at one of these centres. The need for a national arthroplasty register in a country where more than 40,000 hip replacements are performed annually has become more obvious with failure of the Capital hip.